Tobacco use at Fort Riley: a study of the prevalence of tobacco use among active-duty soldiers assigned to Fort Riley, Kansas - Ornelas, Samuel; Benne, Paul D.; Rosenkranz, Richard R. (My University, 2012)
Background: Tobacco use among military personnel is of concern given its substantial burden on military health care and combat readiness. Objective: This cross-sectional study investigated the prevalence of tobacco use and interest in tobacco cessation among active duty soldiers assigned to Fort Riley. Methods: Participants completed tobacco use questionnaires as part of a Soldier readiness process. SPSS v. 16.0 was used to calculate mean percent and multinomial logistic regression analysis. Results: A total of 6,181 active duty soldiers participated in the study (91.2% male, mean age 26.8 years (SD = 6.8 years; range 17-56 years). Forty-nine percent reported using some form of tobacco (smoked tobacco or smokeless tobacco). Smoked tobacco use was 39%. Smokeless tobacco use was over 19%. Thirty-six percent of tobacco users reported interest in cessation. Conclusion: Results suggest that active duty soldiers serving at Fort Riley Army Post represent a high-risk population for tobacco use and there may be unique factors contributing to greater tobacco use and low interest in tobacco cessation. The observed increased use in the time period around deployment provides important information for local health care providers that can be used to tailor current prevention and cessation programs.
Keywords: Tobacco use; Military personnel